Revisão taxonômica das espécies de Canthon Hoffmannsegg do grupo septemmaculatus Latreille (Coleoptera: Scarabaeidae: Scarabaeinae: Deltochilini) - Nunes, Luis Gabriel Oliveira Albuquerque (2015)
The Scarabaeinae subfamily comprises about 7.000 species. They are popularly known as dung beetles, detritivore animals which play an important ecologic function and are also an indicator of environment quality. The Canthon Hoffmannsegg genus, belonging to the Deltochilini tribe, includes more than 170 species, belonging to nine subgenera e some isolated groups, who have no position in the genus, such as septemmaculatus Halffter & Martínez group. The proposed group was originally formed by four species and six subspecies. The objectives of this research were taxonomically review the species septemmaculatus group and set new limits for the group. In order to proceed with the taxonomic review, a comparative analysis of the external and males internal morphology was made, as well of the geographic distribution of the analysed specmens. We present a diagnosis to the septemmaculatus group, establishing morphologic limits to define the species that composes it. Now the group comprising ten species, which can be divided into three subgroups according to the characters of the genitalia. The species Canthon denticulatus, C. principais and C. velutinus do not anymore belong to the group, remaining without a defined group in the genre. Canthon triangularis is now included in the group. The subgroups now have the following composition: a subgroup with four species (Canthon unicolor Blanchard, C. tristis Harold stat. rev. of which C. fortemaginatus Balthasar is a new syn.) and two new species, Canthon sp. new. 1 and Canthon sp. new 2; another subgroup with two species (Canthon monilifer Blanchard (Canthon cincticolle Lucas new syn.) and Canthon triangularis (Drury), the latter including two sub-species; Canthon triangularis triangularis (Drury) and Canthon triangularis paramaribous (Herbst) new stat. and new comb., and even Canthon triangularis flavipellis which is incertae sedis within this species); finally a last subgroup also with four species (C. septemmaculatus Latreille, C. linearis Schmidt new stat. (new syn.; Canthon septemmaculatus maculicollis Schmidt e Canthon septemmaculatus niger Schmidt), C. histrio (Lepeletier de Saint Fargeau & Audinet-Serville) stat. rev. (Canthon septemmaculatus maculipennis Schmidt new syn.) and Canthon sp. new 3). There were designated lectotypes for the following names: Canthon opacus Lucas; Canthon fortemarginatus Balthasar; Canthon costulatus Lucas; Canthon unicolor Blanchard; Canthon cincticollis Lucas; Canthon monilifer Blanchard; Canthon triangularis caliginosus Schmidt; Canthon triangularis flavipellis Schmidt; Ateuchus histrio Lepeletier de Saint Fargeau & Audinet-Serville; Ateuchus fasciatus Mannerheim; Canthon septemmaculatus maculipennis Schmidt; Canthon septemmaculatus linearis Schmidt; Canthon septemmaculatus maculicollis Schmidt; Canthon septemmaculatus niger Schmidt; Ateuchus septemmaculatus Latreille. There were designated neotypes for the following names: Scarabaeus triangularis Drury, Scarabaeus paramaribous Herbst e Scarabaeus sexpunctatus Oliver. After this revision, the septemmaculatus group has ten species, one of them with two subspecies.